Effects of Explicit Sponsorship Disclosure on User Engagement in Social Media Influencer Marketing - Cao, Zike; Belo, Rodrigo (MIS Quarterly, 2024)
Social media influencer marketing has grown substantially in the last decade and is a major advertising channel for many brands. Social media influencers weave sponsored posts with organic content into their feeds, which raises concerns among regulators and consumer advocates that users may not be able to clearly distinguish between sponsored and organic influencer content. Thus, regulators often mandate the explicit disclosure of sponsored content. However, there is little empirical evidence based on field data about the effects of explicit sponsorship disclosure. Therefore, we empirically investigate the effects of explicitly disclosing sponsorship in influencers’ content on users’ engagement using a large-scale field dataset collected from Facebook and Instagram. Our empirical results suggest that explicit sponsorship disclosure increases user awareness of the advertising nature and earns users’ favorability by enhancing transparency about the sponsored content. We further designed two online experiments to corroborate our empirical results and directly test the underlying mechanisms. Our findings have novel and important implications for marketers, influencers, social media platforms, and regulators in the influencer marketing industry.